STUDY OF THE PROPERTIES OF SEMICONDUCTOR MATERIALS USING THE METHOD OF NUCLEAR GAMMA RESONANCE SPECTROSCOPY - Turayev Ergash Yuldashevich; Eshmuhammadova Gulsunoy Xurram qizi (Scholar Express Journal, 2021)
The state of the compound iron atoms inserted into the semiconductor is dependent on the kind of conductivity and the placement of the compound atoms in the surface layer or in the material, according to the data obtained using the nuclear gamma resonance spectroscopy method.
Keywords: Energy state; Resonance; gamma; surface